Impact of Covid-19 on changes in stock prices and the volume of transactions In BUMN (lQ45) - Dheo Rimbano; Weni Susanti; Yuli Nurhayati; Catur Windaryadi; Rudi Azhar (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The problems in this study are the decrease in the share price and the increase in the volume of stock transactions in BUMN listed in LQ45 as well as the number of positive confirmed cases of fluctuating COVID-19 affected by the spread of COVID-19 which is increasingly widespread, causing a higher level of panic in the capital market. This research uses quantitative research methods with comparative and associative research types. This data collection is by observation and documentation with a span of 60 days. Based on the results of the paired t-test, it shows that the comparison between the share price before and after the national announcement of COVID-19 cases in Indonesia has a value (sig.) of 0.000 < 0.05. Based on the results of the wilcoxon signed rank test, it shows that the comparison between the volume of transactions before and after the national announcement of COVID-19 cases in Indonesia has a value (sig.) of 0.000 < 0.05. Based on the results of the Regression Weights in path analysis, it shows that the Stock Price variable has a standardized Regression Weights value of -0.438, and the transaction volume variable has a value of 0.650. So it can be concluded that there is a significant difference between the share price and volume in BUMN registered in LQ45 before and after the national announcement of COVID-19 cases in Indonesia, and there is a significant influence between the number of positive confirmed cases of COVID-19 on the share price and the volume of transactions in BUMN registered in LQ45 during the COVID-19 pandemic in Indonesia.